Supra-Clavicular Artery Flap in Head and Neck Reconstruction - Muhammad Naveed Shahzad , Muhammad Sabir ,Muhammad Jamil Zahid (Journal of Rawalpindi Medical College, 2016)
Background:To study results of supraclavicular artery flap in head and neck reconstruction in terms of its reliability, clinical applications, and functional and aesthetic outcome Methods: In this descriptive study 71 patients who got supraclavicular flap reconstruction were included. When both supra-clavicular areas were found to be suitable for flap donation, the nondominant side was selected as the donor site. In case of patients having only one supraclavicular area suitable for flap donation, that available donor-site was used. Pre-operatively, a 10 MHZ hand held Doppler probe was used to exactly locate and mark the origin and course of the supraclavicular vessels, and flap design was outlined on the selected donorsite according to the analyzed dimensions of the defect. Per-operatively, the defect was prepared and its dimensions were mapped out with the help of a template. The planning in reverse was used to confirm or correct the flap design already marked. The flap was elevated and inset into the defect with a suction drain underneath. The donor site was widely undermined and closed directly in most of the cases with another suction drain in place. Where primary closure was not achievable or considered unsafe even after wide undermining, the defect was reduced in size with advancement of the surrounding skin margins and the residual defect was split-skin grafted. Postoperatively, patients were observed for survival of the flap, and any early flap or donor-site complication. The patients who underwent release of neck contractures were advised to wear a Philadelphia neck collar two weeks postoperatively. At each follow-up, the flap and donor site were examined for any late complications. Results: All flaps survived with only 5 flaps having marginal tip necrosis with acceptable postoperative course